2011
DOI: 10.1158/1078-0432.ccr-11-0557
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Rac GTPase-Activating Protein 1 Is Significantly Associated with the Early Recurrence of Human Hepatocellular Carcinoma

Abstract: Purpose: To assess the significance of Rac GTPase-activating protein 1 (RACGAP1) expression in identifying HBV-positive human hepatocellular carcinoma (HCC) patients who are at high risk for recurrent disease.Experimental Design: The prognostic significance of RACGAP1 was compared with clinicopathologic parameters available at diagnosis using multivariate and log-rank test. RACGAP1 expression and outcome in recurrence was compared between 35 patients with recurrence and 41 patients without recurrence using Kap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
125
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 34 publications
(36 reference statements)
10
125
0
Order By: Relevance
“…Additionally, we consider one of the reasons for this discrepancy is that RACGAP1 has twenty-nine splice variants, and the primer for RACGAP1 described by Ke HL et al [7] used in the present study detects most splice variants. RacGAP1 is reportedly associated with more aggressive cancer phenotypes of high-grade breast cancer [26], epithelial ovarian cancer [27], and hepatocellular carcinoma [15] in the transition from low invasive to high invasive disease. In subgroup analysis of 113 patients with diffuse type gastric cancer, we observed that RacGAP1 IHC scores in patients with lymph node metastasis and vascular invasion were significantly higher than scores in patients without them (cut-off: median value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we consider one of the reasons for this discrepancy is that RACGAP1 has twenty-nine splice variants, and the primer for RACGAP1 described by Ke HL et al [7] used in the present study detects most splice variants. RacGAP1 is reportedly associated with more aggressive cancer phenotypes of high-grade breast cancer [26], epithelial ovarian cancer [27], and hepatocellular carcinoma [15] in the transition from low invasive to high invasive disease. In subgroup analysis of 113 patients with diffuse type gastric cancer, we observed that RacGAP1 IHC scores in patients with lymph node metastasis and vascular invasion were significantly higher than scores in patients without them (cut-off: median value.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RacGAP1 is involved in cell transformation, motility, migration, and metastasis [9][10][11][12]. The clinical significance of RacGAP1 has been reported in several malignancies such as meningioma, breast cancer, and hepatocellular carcinoma [7,8,[13][14][15]. The previous studies suggested that high RacGAP1 expression reflected increased aggressiveness of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…PRC1 has been shown to overexpress in various cancers including breast cancer (8), bladder cancer (9), hepatocellular carcinoma (10,11) and pancreatic cancer (12). The previous study (13) showed that PRC1 was up-regulated in primary gastric cancers and overexpression of PRC1 in gastric cancers was associated with poor disease-specific survival and OS.…”
Section: Original Articlementioning
confidence: 99%
“…There is an existing literature showing that the PI3K/AKT pathway is an important component of RacGAP1 signaling (38). However, whether PI3K/AKT signaling lies upstream or downstream of the Rho family of GTPases remains less clear and appears to be context-specific (38).…”
Section: Racgap1 Modulates Doxorubicin Sensitivity Via Downstream Actmentioning
confidence: 99%
“…However, whether PI3K/AKT signaling lies upstream or downstream of the Rho family of GTPases remains less clear and appears to be context-specific (38). Dysregulation of the PI3K/ AKT pathway is a common event in HNSCC, which can be attributed to multiple factors, such as mutations, amplifications, and signal-induced activation of the pathway (39).…”
Section: Racgap1 Modulates Doxorubicin Sensitivity Via Downstream Actmentioning
confidence: 99%